Geographic variation in West African Agama picticauda: insights from genetics, morphology and ecology. Issue 1 (9th August 2019) - Krishnan, Sneha; Ofori-Boateng, Caleb; Fujita, Matthew K; Leaché, Adam D
ABSTRACT: West Africa is a region characterised by high species diversity and endemism, making it an ideal region to study the evolution of genetic and phenotypic differentiation. Species in this region often vary in morphology and genetics; however, the specific drivers of these differences have not been clearly identified. Focusing on populations in Ghana, we tested for correlations between geography, genetic diversity, morphology and ecology in the West African rainbow lizard ( Agama picticauda ). Genetic data were collected from 102 specimens using double-digest restriction site-associated DNA sequencing (ddRADseq) and the final data matrix included 5 976 loci and 20 624 single nucleotide polymorphisms (SNPs). Morphological data were collected from 42 specimens and included 6 meristic and 4 mensural characters. Ecological data were obtained from the WorldClim database to a resolution of 30 arcseconds. Population structure analyses supported up to five distinct populations of A. picticauda in Ghana. Discriminant function analyses were used to classify samples using the morphological data and ecological data. Ecology showed the strongest correlation with population genetic structure, whereas morphological data were only able to weakly differentiate three populations. We discuss the factors that might be responsible for correlations between phenotypes and genotypes in the context of A. picticauda natural history.